Pengaruh Penerapan Good Governance, Sistem Akuntansi Keuangan Daerah, Dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Keuangan Pemerintah Daerah (Studi Kasus Pada SKPD Kabupaten Gunungkidul) - Eka Puteri Ardianti (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to find out more about the influence of the implementation of good governance, regional financial accounting system, and utilization of information technology to the quality of local government financial statements, given the quality of financial statements can build public confidence in the performance of local governments. The data used in this study are primary data form the results of questionnaires. Respondents in this study are structural officials and officials who perform the functions of accounting / financial administration in each of the Gunungkidul district. The questionnaires was distributed to 45 respondents and data that can be processed as many as 43 questionnaires. The sampling method using Purposive Sampling. Data analysis techniques in this study using multiple linear regression techniques. Results of regression analysis shows that the implementation of good governance does not affect the quality of financial statements of the local government of Gunungkidul district while the regional financial accounting system and utilization of information technology affect the quality of local government financial statements Gunungkidul district.